2012
DOI: 10.1007/s10815-012-9781-3
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of chromosomal abnormalities diagnosed after spontaneous abortions in an infertile population

Abstract: Purpose To estimate the prevalence of chromosomally abnormal related miscarriages in an infertile population. Methods Retrospective analysis of cytogenetics obtained by chorionic villi harvesting of the first miscarriage cycle of infertile patients at our center from 2001-2010 were reviewed. Abnormal results were characterized as trisomy, monosomy X, structural, or other. Age, # of eggs, #2PN, # embryos transferred, day of transfer, and performance of intracytoplasmic sperm injection (ICSI) were recorded. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 10 publications
0
31
1
2
Order By: Relevance
“…Since the incidence of aneuploidy for products of conception is high, 50-80 % [4][5][6][7] it is expected that a reduction of aneuploid embryos might lead to a decreased incidence of pregnancy loss and an increased incidence of LDPS (Fig. 2).…”
Section: Delivery Per Embryo Transferredmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the incidence of aneuploidy for products of conception is high, 50-80 % [4][5][6][7] it is expected that a reduction of aneuploid embryos might lead to a decreased incidence of pregnancy loss and an increased incidence of LDPS (Fig. 2).…”
Section: Delivery Per Embryo Transferredmentioning
confidence: 99%
“…For women over the age of 40 in the United States, roughly half of all clinical pregnancies established through IVF are lost, failing to result in live births (SART CORS Clinic Summary Report, 2012). It has been reported that approximately 50-80 % of all first trimester pregnancy losses result from chromosomal abnormalities in the developing fetus [4][5][6][7]. These abnormalities are a concern for couples seeking IVF treatment to conceive a healthy viable pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Central to the significance of this work was the fact that culturing products of conception (POC) and the methods used to perform cytogenetic testing were maintained throughout the five series of materials analyzed covering a time period of some 40 years and including a total of 8319 SABs. Excepting for the apparent increased incidence of trisomies over time, revealed to be due to increased maternal age in the later study groups, this body of work reaffirmed in the author's own words Bthat the primary determinants of chromosome abnormality are hard-wired into our species.Î nterestingly, the patterns of specific chromosomes implicated in SABs are not unlike that observed in trophectoderm biopsies of ART produced blastocysts [4] and are comparable to what is found in SABs of an infertile population of women [5]. Collectively, then, it seems that our genetics are at play in the everyday world of pregnancy failure, independent of whether conceptions are a byproduct of natural mating, or ART mediation for the subfertile-waiting-to-be-infertile seeking medical intervention.…”
mentioning
confidence: 62%
“…Нарушение деления и повреждение хромосом происходит на этапах оогенеза, сперматогене-за и/или эмбриогенеза и приводит к анэуплоидии у плода. Наиболее распространены среди них трисомии (синдром Дауна, синдром Патау, синдром Эдвартса) и моносомии (синдром Шерешевского -Тернера) [15][16][17].…”
Section: б прегравидарная подготовка женщин с привычным невынашиваниunclassified